Cloud Services in Educational Settings: A Must for Future Nursing Training - Oksana Zhernovnykova; Nataliya Yuhno (Centre for Behaviour and Wellness Advocacy, 2016)
This paper presents research directions from both domestic and foreign scientists regarding the preparation of future nurses to work with cloud services. It also suggests possible ways of implementing these services in their future professional activities. Results from this paper constructively discusses the technical integration challenges of cloud environments with existing systems. It also explores in details, the performance of cloud services and the benefits of their use in modern medicine. This paper has implications for health, cloud services and software engineering.